Temporally gated offline engram ensemble reverberation in the lateral amygdala is required for fear memory consolidation - Sungmo Park; Bozhi Wu; Sofiya Zbaranska; Joseph Lee; Alexander D. Jacob; Annelies Hoorn; Andrew Mocle; Alessandro Luchetti; Mahe Chen; Jung Hoon Jung; Paul W. Frankland; Sheena A. Josselyn (Proceedings of the National Academy of Sciences, 2026)
Memories are encoded by sparsely distributed neuronal ensembles, or engrams, yet how newly allocated engram neurons are consolidated to support subsequent memory retrieval remains unclear. While offline reactivation has been extensively studied in hippocampal circuits, whether similar ensemble-level dynamics support consolidation of emotional memories in the amygdala is unknown. Here we combine longitudinal in vivo calcium imaging, temporally precise activity-dependent neuronal tagging, and optogenetic manipulations to examine postlearning dynamics of fear engram ensembles in the lateral amygdala (LA) of mice. We find that neurons allocated to a fear engram exhibit a transient, temporally gated increase in spontaneous activity and functional coordination immediately after learning, which decay within hours. Disrupting LA activity during this early posttraining window, but not at later time points, produces persistent amnesia. Selective inhibition of neurons active immediately after training is sufficient to impair memory, whereas inhibition of neurons active 12 h posttraining or neurons responsive to an unrelated sensory stimulus has no effect. Critically, memories disrupted by posttraining engram inhibition cannot be rescued by direct optogenetic reactivation of the engram ensemble, indicating a failure of engram consolidation rather than a retrieval deficit. We further show that engram ensemble activity is similarly required following memory retrieval, implicating a shared circuit-level mechanism for consolidation and reconsolidation. Together, these findings identify offline engram ensemble reverberation in the LA as a causal mechanism for transforming a transient, cellularly allocated trace into a stable, retrievable emotional memory.